2021
DOI: 10.1155/2021/4181196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sijunzi Pills on Pharmacokinetics of Omeprazole in Beagle Dogs by HPLC-UV: A Herb-Drug Interaction Study

Abstract: A sensitive high-performance liquid chromatography (HPLC-UV) method for determination of omeprazole in beagle dog plasma was developed and to investigate the effect of Sijunzi pills (SJZPs) on the pharmacokinetics of omeprazole in beagle dogs. The beagle dog plasma was extracted with ethyl acetate and n-hexane under alkaline conditions. Omeprazole and internal standard (IS, fluconazole) were separated on an XDB-C18 column, and acetonitrile and 0.1% trifluoroacetic acid were used as the mobile phase. Omeprazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“… 24 Sijunzi pills could inhibit the metabolism of omeprazole and increase the concentration of omeprazole in beagle dogs. 25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 Sijunzi pills could inhibit the metabolism of omeprazole and increase the concentration of omeprazole in beagle dogs. 25 …”
Section: Resultsmentioning
confidence: 99%
“…24 Sijunzi pills could inhibit the metabolism of omeprazole and increase the concentration of omeprazole in beagle dogs. 25 Tazemetostat is a first-in-class small molecule enhancer of EZH2 inhibitor. 11 The most common treatment-related adverse events (AEs) were asthenia, anemia, anorexia, muscle spasms, nausea, and emesis, which were mostly grade 1 or 2 in severity.…”
mentioning
confidence: 99%
“…Our previous research results showed that Danzhi Xiaoyao pills can accelerate the metabolism of venlafaxine in beagle dogs, reduce the plasma exposure of venlafaxine, and increase the content of O-desmethylvenlafaxine (ODV) and N-desmethylvenlafaxine (NDV) [ 19 ]. Sijunzi Pills could inhibit the metabolism of omeprazole and increase the concentration of omeprazole in beagle dogs [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…e main methods used to detect duloxetine hydrochloride were HPLC [13] and LC-MS [14][15][16]. UPLC-MS/MS technology was a common method for drug-drug interactions (DDIs) and herb-drug interactions (HDIs) [17][18][19](Ruan et al; Xia et al, 2021;Zhu et al, 2019). So, in this study, we optimized the methodology according to the concept and principles of Green Analytical Chemistry (GAC) [20] and established a UPLC-MS/MS for the simultaneous determination of duloxetine as well as its metabolite 4-hydroxyduloxetine in beagle dog plasma.…”
Section: Methods Validation and Improvementmentioning
confidence: 99%